The effects of shoulder and hip widths on the acetabular angle in hip arthroplasty performed in the lateral decubitus position. Trochanter/shoulder ratio effect on postop inclination - Polat , Abdulkadir; Misir , Abdulhamit; Buyukkuscu, Mehmet Ozbey; Fidan, Firat; Basilgan , Seckin (Annals of Medical Research, 2022)
Aim:  This study aimed to determine the effects of the soft tissue and bone widths of the patient's hip and shoulder region on the patient's position and postoperative acetabular inclination angles in the lateral decubitus position during hip replacement procedures. Materials and Methods: Seventy-three patients with primary coxarthrosis who underwent primary hip arthroplasty by a single experienced surgeon using a water gauge assisted inclinometer in lateral decubitus position were retrospectively studied.Soft tissue and bone widths of the shoulder, ASIS (Anterior superior iliac spine), and trochanter levels measured from the preoperative radiographs of the patients and shoulder/hip (ASIS-trochanter) ratios were calculated and made statistical comparisons with postoperative acetabular inclination angle. Results: Postoperative inclination angle had a strong negative correlation with trochanter/shoulder soft tissue ratio, a moderate negative correlation with ASIS/shoulder soft tissue ratio, and a weak negative correlation with trochanter and ASIS/shoulder bone ratios.When patients are grouped by trochanter/shoulder ratio, the postoperative inclination value is 43.04 (38-47) degrees in the group with the ratio < 0.85, the postoperative inclination value is 38.67 (33-45) degrees in the group with the ratio of 0.85-1, and the mean postoperative inclination value in the group with the ratio > 1 was found to be 35.60 (30-38) degrees. (p < 0.001)As for the postoperative inclination values, the mean trochanter/shoulder and ASIS/shoulder values in the group with < 40 degrees were 0.99 and 0.94, respectively, while these values in the group with > 40 degrees were 0.83 and 0.79, respectively. (p < 0.001). Conclusions: Soft tissue widths in the shoulder and hip regions may affect the surgical position and postoperative acetabular inclination angle. Knowing the relationship between the patient's preoperative hip and shoulder distance can influence the expected clinical outcome after hip arthroplasty. Therefore, surgeons should consider these effects when planning hip arthroplasty surgery.
Keywords: Total hip arthroplasty; acetabular inclination; lateral decubitus position; hip width